DETERMINANTS OF TAXPAYER COMPLIANCE AMONG E-COMMERCE MICRO, SMALL, AND MEDIUM ENTEPRISES IN JAKARTA - Devi Damayanti; Indra Pahala; Nuramalia Hasanah (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2026)
This study examines the effects of tax understanding, perceived tax fairness, tax awareness, and tax sanctions on taxpayer compliance among e-commerce Micro, Small, and Medium Enterprises in Jakarta, motivated by a sharp decline in Annual Tax Return compliance among non-employee individual taxpayers. Using a quantitative survey method with purposive sampling, 172 valid responses were analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that tax sanctions are the strongest determinant of compliance, followed by tax awareness and tax understanding, while perceived tax fairness shows no significant effect; together, the four variables explain a substantial proportion of the variance in taxpayer compliance. These findings extend Compliance Theory to the context of e-commerce Micro, Small, and Medium Enterprises under a turnover-based final tax scheme and indicate that enforcement and awareness based approaches may be more strongly associated with compliance than fairness perceptions in this setting, a pattern that should be interpreted with caution given the cross-sectional design of the study. The findings offer practical implications for tax authorities and related institutions in designing compliance strategies for the growing e-commerce MSME sector.